Physicochemical and Structural Investigation of Argeli (Edgeworthia gardneri) Bast Fibers - Gautam, Prakash; Groβmann, Lucas; Pradhan, Sharmila; Bhandari, Netra Lal; Nase, Michael; Adhikari, Rameshwar (Journal of Research Updates in Polymer Science, 2024)
The structure and some physicochemical properties of Argeli (Edgeworthia gardneri) bast fibers were investigated using Fourier Transform Infrared (FTIR) and Energy Dispersive X-ray (EDX) spectroscopies, Optical Microscopy (OM) and Scanning Electron Microscopy (SEM). The neat fibers were found to contain about 54.47% cellulose, 25.98% hemicellulose, 10.5 % lignin, 6.1% extractives, and about 2.9% ash. The fibers on chemical treatments changed several properties, some of them being quite significant. Fiber density was increased by 8.5% in the alkali-treated samples which may be due to the loss of less dense components such as lignin and hemicelluloses. The tensile strength of the fiber increased by 34 % and 61 %, respectively, after alkali and bleaching treatments. However, the thermal properties of treated samples did not change significantly. The mechanical properties of Argeli fiber were improved on chemical treatments making them attractive in the fabrication of polymer composites, textiles, and papers.